Strategic management and regulation of Antarctic tourism - Jabour, J (Springer, 2014)
Antarctic tourism is mainly ship-based and managed on a day-to-daybasis by the industry using guidelines for behaviour designed specifically fortourist sites. Regulation comes mainly from international shipping law. There areincreasing concerns about climate change, shipping accidents and growing touristnumbers, prompting calls for stricter governance to manage growth and risk.The Antarctic Treaty Consultative Parties collaborate with expert organisations togovern tourism but there are still regulatory lacunae that need attention. Initiativessuch as a ban on heavier fuel oils in the Antarctic Treaty area and the impositionof a mandatory shipping code will slowly fill that gap. But a new suggestion isoffered here to tighten regulation even further: the adoption of sponsoring statesfor tourism operators from among Antarctic Treaty Consultative Parties. Thisscheme will introduce a strict element of environmental liability for tourist activities,with greater enforceability.